Caracterização acessos de sisal usando descritores da planta e da fibra - Carneiro, Janáira Lopes dos Santos (2016)
Agave sisalana Perr., belongs to the Agavaceae family, and has a center of plant diversity in Mexico. In Brazil, the first seedlings were introduced in the Northeast, specifically in Bahia, in 1903. Sisal is a species known for its production of lignocellulosic fibers. The by-product, result of the defibration of sisal leaves, is an alternative source for biogas procdution, pharmaceutical input and as composite used in civil construction. In the leaf juice a high pharmacological potential such as inulin and hecogenin was quantified - precursor in the synthesis of corticosteroids. Some studies regarding sisal fibers and their input with pharmacological potential are described in the literature, however studies on the characterization of A. sisalana, in particular regards to morphological, biochemical and physical plant in nature is incipient. Therefore, the present work attempt to identify new applications for sisal by pre-breeding studies by morphological analysis of the plants and to study the morphology of their fibers, analyzing their microstructures, as well as mechanical fiber studies. Morphological analyzes showed that there is variability and heterogeneity among populations, and small plants has higher sugar content and maximum mechanical resistance of the fibers. Mechanical properties studied indicate that fibers vary within and among genotypes of different areas. Morphological and microstructural analyzes of fibers showed that evaluated areas, as well as the distinct regions of apex and base of fibers, have small differences in micro structural characteristics and that different edaphoclimatic conditions do not interfere in the chemical constitution, but intervene in the amount of organic compounds among individuals.